Entrecruzamentos temporais e resiliência no processo de biografização de jovens em situação de risco e de vulnerabilidade social - Pinto, Elismária Catarina Barros (2019)
This thesis is the result of a qualitative research (BOGDAN AND BIKLEN, 1994; DENZIN AND LINCOLN, 2006; MINAYO, 2009) that aimed, in a comprehensive approach and impregnated by affections, to expound the self narratives built by young people from Maracanaú, a city located in the metropolitan area of Fortaleza, capital of Ceará. These young people were attended by the Serviço de Convivência e Fortalecimento de Vínculos (SCFV), that is held by a Centro de Referência em Assistência Social (CRAS). The study aimed to understand, by the life’s history of five young people, the meaning of different agents and institutions in their lifepathes and how they contributed for a resilient answer to the situations of risk and social vulnerability that these people were/are exposed. The self narratives were built in a process called Círculo Reflexivo Biográfico - CRB (OLINDA, 2018), that happened between the second semester of 2017 and the first semester of 2018. Knowing the complexity of the investigated context and the need to embark on dialogic pathways that allow the comprehension of meanings inscribed in the narrated experiences, I choose, in the qualitative research universe, the (auto)biographic research in educational context. The narrative showed itself a gifted way to access the young people’s lifestyles and to the self invention processes. The theorical approach is based on two basis: a) the epistemological, theorical and methodological elaborations of authors linked to the socioeducative theorical current of life stories under development - Delory-Momberger (2006, 2008, 2014); Josso (2010); Pineau (2010, 2012); Passeggi (2011, 2016) e Olinda (2010, 2016, 2017 e 2018) and b) the authors of sociology of youth - Pais (1990, 2000), Groppo (2004), Adorno (2001). Also laws from the Estatuto da Criança e do Adolescente and from the Estatuto da Juventude were important for analysis, as well as the data from the “Cada Vida Importa” report, made by the Comitê Cearense de Prevenção a Homicídios na Adolescência of Ceará’s parliament. The guiding question of this study was: which events, beliefs, people and institutions were more significant in the answers from the young people in a situation of risk and of social vulnerability? Guided by the paradigm of singular-plural (FERRAROTTI, 2010), I aimed to understand the young people’s life based on a documental research, as well as on a bibliographic review, to situate them on the socioeconomic scenery of the city where they live. The corpus was analyzed by the discursive textual analysis (MORAES, 2003; MORAES AND GALIAZZI, 2006), indicating the following categories: denial of fundamental rights; conflicting family relationships; presence of resilience tutors and the power of beliefs and religious belonging. The life stories of young people, although being marked by successive denials of rights, showed processes of resilience that were 13 results of a combination of family, religious and social factors. The social projects weren’t highlighted as significant experiences on the youth narratives.